The Social Harms of Academics’ Abuse in Nigerian Universities: Failed Ethical Leadership - Success Ayodeji Fasanmi; Sadi Seyama (Studies in Learning and Teaching, 2023)
Universities are higher institutions where a high level of manpower training is provided for the development of the total man. At the centre of this is the role of academic members. The three core functions of the academic staff are teaching, research, and service. Over the years, there have been cases of abuse of academics in Nigerian universities, which has been a source of concern to relevant stakeholders. Abuse of Academics is any form of unethical treatment given to university academics in the course of discharging their duties. The study argues that the abuse of academic staff indicates failed ethical leadership. Drawing on the social harms theory, it provides evidence of the hazardous use of power against academics. In this case study of Obafemi Awolowo University, thirty academic staff across all cadres and genders were interviewed. The findings reveal that academic abuse has been an age-long problem in Nigerian universities. The study further shows the causes of academic abuse to be rooted in the fact that the government does not prioritise education, which makes its budgetary allocation to the sector very ridiculous.